Milton Friedmans economics and political economy: an old Keynesian critique - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
Milton Friedman's influence on the economics profession has been enormous. In part, his success was due to political forces that have made neoliberalism the dominant global ideology, but Friedman also rode those forces and contributed to them. Friedman's professional triumph is testament to the weak intellectual foundations of the economics profession which accepted ideas that are conceptually and empirically flawed. His success has taken economics back in a pre-Keynesian direction and squeezed Keynesianism out of the academy. Friedman's thinking also frames so-called new Keynesian economics which is simply new classical macroeconomics with the addition of imperfect competition and nominal rigidities. By enabling the claim that macroeconomics is fully characterized by a divide between new Keynesian and new classical macroeconomics, new Keynesianism closes the pincer that excludes old Keynesianism. As long as that pincer holds, economics will remain under Friedman's shadow.
urn:nbn:de:101:1-2014080818024
Keywords: 330; Friedman; monetarism; new classical macroeconomics; new Keynesian; neoliberalism